2008
DOI: 10.1063/1.2990762
|View full text |Cite
|
Sign up to set email alerts
|

Submicrometer periodic patterns fixed by photopolymerization of dissipative structures

Abstract: In photoreactive liquid crystals, spontaneous pattern formation can be used to fabricate phase gratings or polymer films with a periodic surface modulation. Typically, the periodicity of such structures is comparable to the sample thickness, and thus in the range between several micrometers and about 100 μm. Here, attempts to create and to investigate smaller structures are presented. For a chevron pattern, periodicities as small as 800 nm could be detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Voltages with higher frequencies induce periodic structures without flow, for example, a chevron pattern ͑dielectric regime͒. [17][18][19] The aim of this work was to investigate the stability diagrams in the ͑frequency, voltage͒ plane and the influence of composition and UV intensity on the properties of a simple model system that is particularly suitable for this purpose ͑Table I͒. However, more recent studies reveal the appearance of dissipative structures also in certain liquid crystals with positive dielectric anisotropy [7][8][9] and in liquid crystals with negative anisotropy of the conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Voltages with higher frequencies induce periodic structures without flow, for example, a chevron pattern ͑dielectric regime͒. [17][18][19] The aim of this work was to investigate the stability diagrams in the ͑frequency, voltage͒ plane and the influence of composition and UV intensity on the properties of a simple model system that is particularly suitable for this purpose ͑Table I͒. However, more recent studies reveal the appearance of dissipative structures also in certain liquid crystals with positive dielectric anisotropy [7][8][9] and in liquid crystals with negative anisotropy of the conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…1(a)). [27][28][29][30][31][32][33][34] It has been repeatedly demonstrated that EHD-induced periodic DGs can also be promising for beam steering applications 28 in various optoelectronic devices, such as tunable spectral filters, polarizing sensors, etc. 29 Recently, a fascinating example of light-driven EHD instabilities was demonstrated by G. Zhou et al 30 The LC mixture with a high negative dielectric anisotropy (De = À8.3) was doped with the spiropyran photochromic substance.…”
Section: Introductionmentioning
confidence: 99%
“…Among all, LC-based devices are more economical and efficient owing to their reliability, cost effectiveness, and low operating voltage requirement . The mechanical and thermal properties of LCs are further enhanced by combining them with polymer materials to form liquid crystal polymer composites (LCPCs) with improved switching properties. These materials have dynamic electro-optic (E-O) properties and are, therefore, excellent candidates for the fabrication of optoelectronic devices. LCPCs have many benefits over conventional LC-based devices, such as nondegradability over time and no requirement of a polarizer in addition to their enhanced resistance to thermal and mechanical stress. …”
Section: Introductionmentioning
confidence: 99%